2020
DOI: 10.1021/acs.iecr.9b03876
|View full text |Cite
|
Sign up to set email alerts
|

Operando Raman Spectroscopy of the Microwave-Enhanced Catalytic Dehydration of 2-Propanol by WO3

Abstract: Operando Raman spectroscopy was performed to understand the mechanism of a microwave (MW)-enhanced fixed-bed catalytic reaction. An MW operando Raman spectroscopy system was constructed by integrating a Raman spectroscopy probe (785 nm) with a single-mode (TM110) MW cavity resonator equipped with a semiconductor MW generator. MW heating enhanced the dehydration of 2-propanol to diisopropyl ether and propylene by +54 to +60% under the air flow condition. In the argon flow condition, the conversion of 2-propanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
2
11
1
Order By: Relevance
“…From the resonance frequency results, together with Raman spectroscopy and MS, we concluded that the WO 3 surface was reduced in tandem with the enhanced dehydration of 2-propanol. Moreover, these results strongly agreed with our previous report on operando Raman spectroscopy (785 nm) of the same reaction . The Raman peak intensity and resonance frequency profiles strongly coincided with the formation of propylene.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…From the resonance frequency results, together with Raman spectroscopy and MS, we concluded that the WO 3 surface was reduced in tandem with the enhanced dehydration of 2-propanol. Moreover, these results strongly agreed with our previous report on operando Raman spectroscopy (785 nm) of the same reaction . The Raman peak intensity and resonance frequency profiles strongly coincided with the formation of propylene.…”
Section: Resultssupporting
confidence: 92%
“…During the first 10 min, the formation of these products strongly correlated with a decrease in the intensity of the Raman spectra. These behaviors are in line with our previous study, which used GC analysis (every 20 min) . Meanwhile, the present MS system allowed time-resolved product analysis (every 3 s), which was useful for tracking the changes in the product distribution along with the oxidation state of the WO 3 catalyst.…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations